The Problem of Developing the Reflexivity of Future Specialists in Social and Humanistic Sciences in the Context of Postmodernism - Illiuschenko, Serhii; Povidaichyk, Mykhailo; Dorosh, Tetiana; Demyanenko, Natalia; Ostapenko, Larysa; Maksymenko, Anatolii (My University, 2021)
The article talks about the postmodern approach to studying the problem of reflexive competence of future specialists, requires a comprehensive analysis of the organization and content of the educational process in higher education institutions. The postmodern concept of professional reflection and personal reflexivity of students is highlighted, it determines the ratio of these formations as unique individual phenomena, their influence on the formation and manifestation of professional and professional competence at the creative- professional, cognitive and personal-motivational levels. The concept of reflectivity of the future specialist is specified. The structure of professional reflection of students is specified. The value of pedagogical practice for the development of professional reflection in future professionals from the standpoint of the postmodern approach is emphasized. The model of formation and development of personal-professional reflectivity in future specialists at the competence, cognitive, personal-motivational, emotional and evaluative-behavioral levels is presented.
The Problem of Developing the Reflexivity of Future Specialists in Social and Humanistic Sciences in the Context of Postmodernism / S. Illiuschenko, M. Povidaichyk, T. Dorosh, N. Demyanenko, L. Ostapenko, A. Maksymenko //. Postmodern Openings. – 2021. – №12(4). Р. 171−183. – Режим доступу : https:∕∕doi.org∕10.18662∕po∕12.4∕367. – Назва з екрана. Web of Science (WOS)
Keywords: самопізнання, саморозуміння, постмодерністська педагогіка, рефлексивна компетентність, освітні потреби, постмодерна концепція рефлексії, рефлексивні навички студентів, професійна рефлексія, особистісна рефлективність, постмодерністський підхід; self-knowledge, self-understanding, postmodern pedagogy, reflexive competence, educational needs, postmodern concept of reflection, reflexive skills of students, professional reflection, personal reflexivity, postmodern approach